2017
DOI: 10.1097/qad.0000000000001569
|View full text |Cite
|
Sign up to set email alerts
|

HIV drug resistance in infants increases with changing prevention of mother-to-child transmission regimens

Abstract: Objectives The objectives of this study were to determine HIV drug resistance prevalence in Zambian infants upon diagnosis, and to determine how changing prevention of mother-to-child transmission (PMTCT) regimens affect drug resistance. Design Dried blood spot (DBS) samples from infants in the Lusaka District of Zambia, obtained during routine diagnostic screening, were collected during four different years representing three different PMTCT treatment regimens. Methods DNA extracted from DBS samples was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
18
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 12 publications
5
18
1
Order By: Relevance
“…As described in a 2017 meta-analyses review, 39 Boerma et al documented increasingly high rates of ARV resistance over the past decade among HIV infected infants and young children (47%) in 13 countries who failed PMTCT; as well as resistant virus among HIV infected children not reported to be exposed to PMTCT antiretrovirals (26.8%).These include studies from Southern and East Africa 4042 as well as West Africa with the highest proportion of resistance being to nonnucleoside Reverse Transcriptase Inhibitors (NNRTIs) followed by Nucleoside Reverse Transcriptase Inhibitors (NRTIs). 4344 Likewise HIV infected pregnant women in international settings have also shown increased rates of resistance to NNRTI and NRTIs’ with a study from KwaZulu-Natal South Africa, 45 reporting 65% of pregnant women having an NNRTI resistance and 7% with TAMS resistance using Ultra-deep sequencing (UDS) assays; and a study from Tanzania reported similar findings with drug resistance mutants in 69% of women based on UDS assays.…”
Section: Introductionmentioning
confidence: 99%
“…As described in a 2017 meta-analyses review, 39 Boerma et al documented increasingly high rates of ARV resistance over the past decade among HIV infected infants and young children (47%) in 13 countries who failed PMTCT; as well as resistant virus among HIV infected children not reported to be exposed to PMTCT antiretrovirals (26.8%).These include studies from Southern and East Africa 4042 as well as West Africa with the highest proportion of resistance being to nonnucleoside Reverse Transcriptase Inhibitors (NNRTIs) followed by Nucleoside Reverse Transcriptase Inhibitors (NRTIs). 4344 Likewise HIV infected pregnant women in international settings have also shown increased rates of resistance to NNRTI and NRTIs’ with a study from KwaZulu-Natal South Africa, 45 reporting 65% of pregnant women having an NNRTI resistance and 7% with TAMS resistance using Ultra-deep sequencing (UDS) assays; and a study from Tanzania reported similar findings with drug resistance mutants in 69% of women based on UDS assays.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of infants to antiretroviral drugs for prevention of mother-to-child transmission (PMTCT) can induce resistance to nucleoside/nucleotide reverse transcriptase inhibitors (NRTIs) [1][2][3][4][5].…”
mentioning
confidence: 99%
“…This may explain the high prevalence of TAMs in our study population. However, the high prevalence of TAMs was reported in an earlier study of adults failing HIV treatment in Lusaka, Zambia and other studies in the region [6,8,9,10,24]. Non the less, the poor documentation of the reasons for drug change in patient medical records remains a major limitation to interpreting the presence/absence of HIVDR mutations including TAMs.…”
Section: Plos Onementioning
confidence: 92%
“…In Johannesburg South Africa, 56.8% of 230 PMTCT-exposed but newly diagnosed children under two years had Non-Nucleoside Reverse Transcriptase Inhibitor (NNRTI) HIVDR. In Zambia, a study of HIVDR in perinatally infected children showed an increasing and worsening pattern of HIVDR from 21% in 2007/9 to 40% in 2014 [10].While these studies contribute to our understanding of drug resistance, only the study in Tanzania included adolescents [11].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation